Answer:
[tex]\dfrac{1}{16}[/tex]
[tex]\dfrac{5}{3}[/tex]
Explanation:
[tex]m_1[/tex] = Mass of first object
[tex]m_2[/tex] = Mass of second object
v = Speed of both objects
[tex]\dfrac{v}{4}[/tex] = Combined velocity
The ratio of final kinetic energy to initial kinetic energy will be
[tex]\dfrac{K_f}{K_i}=\dfrac{\dfrac{1}{2}(m_1+m_2)(\dfrac{v}{4})^2}{\dfrac{1}{2}(m_1v^2+m_2v^2)} \\\Rightarrow \dfrac{K_f}{K_i}=\dfrac{(m_1+m_2)\dfrac{v^2}{16}}{m_1v^2+m_2v^2}\\\Rightarrow \dfrac{K_f}{K_i}=\dfrac{(m_1+m_2)\dfrac{1}{16}}{m_1+m_2}\\\Rightarrow \dfrac{K_f}{K_i}=\dfrac{1}{16}[/tex]
The ratio is [tex]\dfrac{1}{16}[/tex]
As the linear momentum is conserved
[tex]m_1v-m_2v=(m_1+m_2)\dfrac{v}{4}\\\Rightarrow m_1-m_2=(m_1+m_2)\dfrac{1}{4}[/tex]
Divide by [tex]m_2[/tex] on both sides
[tex]\dfrac{m_1}{m_2}-1=\dfrac{m_1}{4m_2}+\dfrac{1}{4}\\\Rightarrow \dfrac{m_1}{m_2}-\dfrac{m_1}{4m_2}=\dfrac{1}{4}+1\\\Rightarrow \dfrac{3m_1}{4m_2}=\dfrac{5}{4}\\\Rightarrow \dfrac{m_1}{m_2}=\dfrac{5\times 4}{3\times 4}\\\Rightarrow \dfrac{m_1}{m_2}=\dfrac{5}{3}[/tex]
The ratio of mass is [tex]\dfrac{5}{3}[/tex]